IDDF2022-ABS-0079 Short-chain fatty acid-producing mixed bacteria improve experimental colitis via promoting M2-like macrophages polarization. (2nd September 2022) - Zhao, Hailan; Xu, Jing; Wang, Jiaqi; Xu, Haoming; Huang, Wenqi; Guo, Xue; Zhang, Yong; Liu, Yandi; Huang, Hongli; Zhou, Youlian
Abstract : Background: There is a decrease in probiotic bacteria, especially the depletion of short-chain fatty acids (SCFAs)-producing bacteria in Inflammatory bowel diseases (IBD). Although intestinal probiotic bacteria have been identified to alleviate colitis, however, the efficacy of mixed SCFAs-producing bacteria in inflammatory patients remains unclear. Methods: We used a reasonable approach to isolate and culture several SCFAs-producing bacteria from the feces of the healthy donors. The objective of this study was to compare the effects of 7-mixed bacteria, mixed supernatant, and human FMT on DSS-induced acute experimental colitis and to explore their mechanisms. Results: We observed that mice gavage with mix-sup, 7-mix and hu-FMT more effectively improved weight loss, DAI scores, colon lengths and colonic inflammation, and less inflammatory cell infiltration than mice gavage with PBS (IDDF2022-ABS-0079 Figure 1a-f. Mix-sup and 7-mix gavage meliorated the DSS-induced acute colitis and enhanced gut barrier). Immunohistochemistry results of ZO-1 and occludin also observed that mix-sup, 7-mix and hu-FMT had more beneficial to gut barrier reinforcement than PBS (IDDF2022-ABS-0079 Figure 1g-h. Mix-sup and 7-mix gavage meliorated the DSS-induced acute colitis and enhanced gut barrier). We further demonstrated that mix-sup, 7-mix and hu-FMT gavage group diminished M1 associated pro-inflammatory cytokines, i.e., iNOS, IL-1β, IL-12, IL-23, IL-6, TNF-α (IDDF2022-ABS-0079 Figure 2a. Mix-sup and 7-mix triggered beneficial role via facilitating an M2-like macrophage response in vivo and in vitro), while promoted the expression of M2-related anti-inflammatory cytokines, i.e., CD206, TGF-β, and IL-5, compared to PBS group in mice acute colitis (IDDF2022-ABS-0079 Figure 2b. Mix-sup and 7-mix triggered beneficial role via facilitating an M2-like macrophage response in vivo and in vitro). Moreover, flow cytometry data further confirmed that intervention of mix-sup and 7-mix obviously promoted M2-like macrophage polarization, and the ratio of M1/M2 further clarified seven strains mixture, especially supernatant mixture play a beneficial role in intestinal barrier repair (IDDF2022-ABS-0079 Figure 2c. Mix-sup and 7-mix triggered beneficial role via facilitating an M2-like macrophage response in vivo and in vitro). To confirm whether mix-sup and 7-mix induced M2-like macrophage (CD206) polarization in vitro, RAW264.7 cells/mix-sup and RAW264.7 cells/7-mix transwell chamber co-culture system was employed (IDDF2022-ABS-0079 Figure 2d. Mix-sup and 7-mix triggered beneficial role via facilitating an M2-like macrophage response in vivo and in vitro). All data clarified mix-sup and 7-mix via facilitating an M2-like macrophage response to alleviate inflammatory in vivo and in vitro . Conclusions: We selected seven probiotic microorganisms and metabolites (SCFAs) that are comparable or superior to FMT in repairing leak gut barrier via facilitating an M2-like macrophage response.